Selective targeting of ASIC3 using artificial miRNAs inhibits primary and secondary hyperalgesia after muscle inflammation - Walder, Roxanne Y. (2011)
Acid-sensing ion channels (ASICs) are activated by acidic pH and may play a significant role in the development of hyperalgesia. Earlier studies show ASIC3 is important for induction of hyperalgesia after muscle insult using ASIC3−/− mice. ASIC3−/− mice lack ASIC3 throughout the body, and the distribution and composition of ASICs could be different from wild-type mice. We therefore tested whether knockdown of ASIC3 in primary afferents innervating muscle of adult wild-type mice prevented development of hyper-algesia to muscle inflammation. We cloned and characterized artificial miRNAs (miR-ASIC3) directed against mouse ASIC3 (mASIC3) to downregulate ASIC3 expression in vitro and in vivo. In CHO-K1 cells transfected with mASIC3 cDNA in culture, the miR-ASIC3 constructs inhibited protein expression of mASIC3 and acidic pH-evoked currents and had no effect on protein expression or acidic pH-evoked currents of ASIC1a. When miR-ASIC3 was used in vivo, delivered into the muscle of mice using a herpes simplex viral vector, both muscle and paw mechanical hyperalgesia were reduced after carrageenan-induced muscle inflammation. ASIC3 mRNA in DRG and protein levels in muscle were decreased in vivo by miRASIC3. In CHO-K1 cells co-transfected with ASIC1a and ASIC3, miR-ASIC3 reduced the amplitude of acidic pH-evoked currents, suggesting an overall inhibition in the surface expression of heteromeric ASIC3-containing channels. Our results show, for the first time, that reducing ASIC3 in vivo in primary afferent fibers innervating muscle prevents the development of inflammatory hyperalgesia in wild-type mice, and thus, may have applications in the treatment of musculoskeletal pain in humans.